'Not a Prophet' versus 'Foreign Fads': two scenarios for conceptualising social pedagogy dissemination - Jacob Kornbeck (Scottish Journal of Residential Child Care)
Against the backdrop of current Scottish and British efforts to establish social pedagogy in higher education and professional practice, these efforts may be met with enthusiasm or reticence. Because Scotland and the UK have no explicit social pedagogy tradition, social pedagogy needs to be imported from countries with such a tradition, which usually means Continental Europe and the Nordic countries. As a framework for understanding how social pedagogy may be seen, the paper develops two scenarios, 'Not a Prophet' (exemplified through the gradual disappearance of social pedagogy in Germany, where it originated) and 'Foreign Fads' (discussed by drawing on an exemplary debate in the magazine Community Care, showing English/British unease with social pedagogy on account of its German and Nordic connotations). The paper insists on the need to adapt social pedagogy to the local context.